Private Regulation on the Environment: Bilateral Voluntary Agreements in U.S. Toxic Chemical Policy - Hsueh, Lily (My University, 2013)
In recent decades, in the backdrop of highly constrained government and public sector finances worldwide, private forms of regulation in natural resource and environmental policy have gained political and public salience: there is an increased interest in governance with government rather than governance by government. This dissertation, consisting of three essays, investigates the policy impact of bilateral voluntary agreements, one form of voluntary environmental programs, and the compliance-related decision-making processes involving regulators, corporate actors, and NGO activists that have led to them. The first essay of the dissertation examines the effectiveness of a bilateral voluntary agreement negotiated between the U.S. EPA and the pressure-treated wood industry to ban the use of a poisonous arsenic compound. Unlike earlier studies on voluntary programs, results from dynamic panel estimation and advanced time series techniques show that the voluntary agreement has lowered arsenic use in the U.S. to levels not seen since the 1920s. Moreover, a government-driven information disclosure policy--namely the EPA's Toxic Release Inventory--was effective in decreasing arsenic use, albeit to a lesser magnitude than the industry voluntary ban. Prioritizing environmental protection through financial resources, as measured by Congress-allocated dollars to the EPA, has also reaped environmental benefits. Systematic surveys of key stakeholders provide institutional, political, and economic insights into the impact estimates of the bilateral voluntary agreement on arsenic use. Policy process tracing based on the survey data shows that the pressure-treated wood industry was compelled to engage in beyond-compliance action given the existence of a poison-free substitute, market competitive pressures, and the threat of future regulation. The EPA regulators casted a shadow of public law with the credible threat of future regulation by "steering" or encouraging voluntary action and sanctioning noncompliance once the voluntary beyond compliance action had occurred. Moreover, third-party stakeholders, such as NGO activists, played an important "accountability" role by pressuring for and certifying firms' beyond compliance environmental stewardship. In the second essay, I develop a theoretical framework by building on the multiple streams framework (Kingdon, 1984) to explain the compliance-related decision-making processes and apply it to two cases of "successful" bilateral voluntary agreements in mercury and arsenic use, respectively. Specifically, to the problem, policy, and politics streams of the multiple streams framework I add an economy stream and delineate its key variables. I argue that the economy stream demarcates the roles that product substitutes, market competition, corporate social responsibility, the market changer, and the global economy play in creating incentives for businesses to partake in industry self-regulation. The market changer is a maverick business that engages in an action or a set of actions that completely transforms the modus operandi of the industry in which the market changer operates. While both bilateral voluntary agreements achieved the negotiated chemical reduction objectives, the push and pull of politics, economics, as well as institutional factors led to two distinctive bilateral voluntary agreements: one was an outcome of industry voluntary stewardship and the other was a result of activist campaigns. The final essay employ recently developed, state-of-the-art structural change and unit root tests, as well as cointegration analyses to investigate whether federal regulations since the 1970s have had an effect on toxic chemical use and what the time series properties of the data reveal about policy efficacy over the long-run. I examine whether there is a long-run equilibrium relationship among chemicals that are regulated under the same laws and whether there are clusters of chemicals (e.g., end-use sectors that use the same chemicals) that share a common trend, which could suggest common economic and institutional drivers. Results indicate that while some toxic chemicals have been successfully reduced or phased-out by regulatory efforts, a majority of the toxic chemicals used in commercial products are largely driven by changes in U.S. GDP, industrial production, and private investments in research and development, rather than by common political, economic, and institutional factors, such as government regulations.
Thesis (Ph.D.)--University of Washington, 2012
Keywords: Environmental economics; Environmental policy; Industry self regulation; Political economy; Private regulation; Toxic chemicals; Environmental economics; Public policy; Environmental management; public affairs